كلمة البصر ومترادفاتها في صحيح البخاري: دراسة لغوية - نور فرحانا بنت أحمد غفار
Synonym is a linguistics feature that studies similarity of meaning between two or more words. The similarity between two or more words can be differentiated through context, which makes it clearer when it involves religious texts for juristic purposes. Various past studies showed that researchers, who focused on synonymy in al-Quran have denied its existence due to the unique meanings of every word. However, for the texts of Hadith, Islamic Scholars have focused more on collecting the Hadith and its description and not focused on synonymy between words. Therefore, this study focuses on the existence of synonyms in Prophetic Hadiths, as the second source of Islamic Law. The objectives of this study are (1) to determine the number of hadiths that possess the word basar and its synonyms, (2) to analyze the hadiths from the morphological aspect, (3) to analyze the semantic aspects of the word basar and its synonyms, and (4) to analyze the uslub insyai and khabari in the word basar and its synonyms. This study uses two methods of analysis, namely Framework Analysis and Start List Form to analyze the word basar and its synonyms in Sahih Bukhari. The results show that there are 221 hadiths that possess the word basar and its synonyms. From the morphological aspect, it shows that there is diversity in the use of nouns and verbs according to the context of Hadith. In addition, the findings of the semantic aspect show that the word basar and its synonyms have almost the same meaning, besides the distinctive connotation assigned to each word. From the aspect of ‘ilm Ma'ani, there is a diversity between khabari and insyai styles for each word, in addition to deviation style. The overall finding proves that there are no two words with the same meaning in the Hadith. Thus, the understanding of the Hadith texts should be done carefully especially when involving words which seem to be synonymous as each word has its own meaning according to the context used. Inaccuracy in this aspect can lead to legal implications.